Patterns and drivers of regeneration of tree species in forests of peninsular Spain - Vayreda, Jordi; Gracia, Marc; Martínez-Vilalta, Jordi; Retana, Javier (Journal of Biogeography, 2013)
Aim Our study aimed to identify and explore the main factors that influence tree recruitment of multiple species at a regional scale across peninsular Spain, an understanding of which is essential for predicting future forest species composition in the face of ongoing environmental change. The study focused on the dynamics of the key transition phase from saplings to adult trees. Location The forests of peninsular Spain. Methods We used the extensive network of plots sampled in two consecutive Spanish national forest inventories (> 30,000 plots) to identify the factors that determine regeneration patterns of the 10 most abundant forest species of Spain at relatively large temporal (c. 10 years) and spatial scales (across Spain): five coniferous species of Pinus (pines) and five broadleaved species of the genera Fagus and Quercus. We fitted separate generalized linear models for the pine species and the broadleaved species to assess the response of sapling abundance and ingrowth rate to the spatial variability of climate (temperature, water availability and recent warming), forest structure (tree density, understorey and overstorey canopy cover, and basal area change) and disturbances (previous forest logging, wildfires and grazing). Results Mean sapling abundance was four times higher for broadleaved species than for pines, while mean annual ingrowth was twice as high. Sapling abundance and ingrowth rate were mainly determined by stand structure, both in pines and broadleaved trees. The direct effects of disturbances and climate were comparatively smaller, and there was no detectable effect of recent warming. Main conclusions The higher values of ingrowth rate of broadleaved species can be explained by their ability to maintain a higher sapling bank due to their greater shade tolerance. This differential response of pines and broadleaved species to canopy closure suggests a probable increase in broadleaved species at the expense of pines. This transition could occur earlier in stands with faster canopy closure dynamics. Spatially explicit, mixed-species demographic models incorporating both the ingrowth and the tree mortality components are needed for predicting the composition of future forests.
Keywords: Broadleaved trees; climate warming; conifers; disturbance; ingrowth rate; national forest inventory; sapling abundance; shade tolerance; Stand Structure; Water availability

Architecture of Iberian canopy tree species in relation to wood density, shade tolerance and climate - Poorter, Lourens; Lianes, Elena; Moreno-de las Heras, Mariano; Zavala, Miguel A. (Plant Ecology, 2012)
Tree architecture has important consequences for tree performance as it determines resource capture, mechanical stability and dominance over competitors. We analyzed architectural relationships between stem and crown dimensions for 13 dominant Iberian canopy tree species belonging to the Pinaceae (six Pinus species) and Fagaceae (six Quercus species and Fagus sylvatica) and related these architectural traits to wood density, shade tolerance and climatic factors. Fagaceae had, compared with Pinaceae, denser wood, saplings with wider crowns and adults with larger maximal crown size but smaller maximal height. In combination, these traits enhance light acquisition and persistence in shaded environments; thus, contributing to their shade tolerance. Pinaceae species, in contrast, had low-density wood, allocate more resources to the formation of the central trunk rather than to branches and attained taller maximal heights, allowing them to grow rapidly in height and compete for light following disturbances; thus, contributing to their high light requirements. Wood density had a strong relationship with tree architecture, with dense-wooded species having smaller maximum height and wider crowns, probably because of cheaper expansion costs for producing biomechanically stable branches. Species from arid environments had shorter stems and shallower crowns for a given stem diameter, probably to reduce hydraulic path length and assure water transport. Wood density is an important correlate of variation in tree architecture between species and the two dominant families, with potentially large implications for their resource foraging strategies and successional dynamics.
Keywords: Architecture; Crown traits; Drought; shade tolerance; Tree height; Wood density

Differential light responses of Mediterranean tree saplings: linking ecophysiology with regeneration niche in four co-occurring species - Gómez-Aparicio, LORENA; Valladares, Fernando; Zamora, Regino (Tree Physiology, 2006)
The ecophysiological mechanisms underlying plant–plant interactions and forest regeneration processes in Mediterranean ecosystems are poorly understood, and the experimental evidence for the role of light availability in these processes is particularly scant. We analyzed the effects of high and low irradiances on 31 ecological, morphological and physiological variables in saplings of four late-successional Mediterranean trees, two deciduous (Acer opalus subsp. granatense (Boiss.) Font Quer & Rothm. and Quercus pyrenaica Willd.) and two evergreen (Pinus nigra Arnold subsp. salzmannii (Dunal) Franco and Quercus ilex L.), which coexist in mature montane forests. Species differed in both their capacity to withstand high radiation and in their shade tolerance. The two deciduous species were the least tolerant to high radiation, exhibiting both dynamic and chronic photoinhibition in full sunlight, with severe implications for gas exchange and photosynthetic performance. Excess light severely limited the survival of A. opalus subsp. granatense, even minor reductions of excessive radiation (from full sunlight to 80% sunlight) being crucial for sapling survival. Among species, P. nigra was the most tolerant of high irradiances but showed the poorest shade acclimation. Interspecific differences in the mechanisms of response to light provide a partial explanation of the differential regeneration patterns previously reported for these species, with shade-tolerant plants (i.e., deciduous broadleaf species) benefiting the most from associations with nurse plants. We conclude that light availability is an important environmental factor defining the regeneration niche of Mediterranean woody species.
10.1093/treephys/26.7.947
Keywords: Acer opalus subsp. granatense; photoinhibition; photosynthetic light response; Pinus nigra; Quercus ilex; Quercus pyrenaica; shade tolerance

ESTRUCTURA Y EVOLUCIÓN DE DOS MASAS MIXTAS DE FRONDOSAS PROCEDENTES DE UN ANTIGUO MONTE ADEHESADO - Hermosilla, D; Pardo, F; Gil, L; Pardos, J A (III Congreso Forestal Español Congreso, 2001)
The presence of an important number of deciduous Central European species in Hayedo de Montejo makes it to be considered a singular place in Madrid. Past traditional practices conditioned the present characteristics of this forest. Two mixed deciduous stands were chosen for its study, both formed by a stratum of old-growth trees and another made up of poles. A vegetation inventory was made around twenty old-growth trees. The influence in the structure and evolution of the stand composed by poles was studied. The species of old-growth tree and the distance were relevant on the structure of the stand grown around them.
Keywords: competition; open wood; shade tolerance